2015
DOI: 10.1039/c5py01398d
|View full text |Cite
|
Sign up to set email alerts
|

The Ugi reaction in polymer chemistry: syntheses, applications and perspectives

Abstract: The Ugi reaction, one of the most famous multicomponent reaction, has recently been introduced into polymer chemistry as a novel, efficient and useful tool to prepare multifunctional polymers. In this review, recent progress on the utilization of the Ugi reactions in polymer chemistry, including monomer synthesis, polycondensation, post-polymerization modification (PPM) etc. has been be summarized. Meanwhile, the applications of multifunctional polymers synthesized via the Ugi reaction and the future developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 88 publications
0
71
0
Order By: Relevance
“…The MCRs could also introduce novel chemical structures and functions in the final products during the procedure of MCRs. More recently, the combination of controlled living polymerization and MCRs has also been demonstrated by Tao and co‐workers . Considered the above described characteristics, we could therefore expect that MCRs may be promising tools for fabrication of various multifunctional AIE‐active FONs in more efficient routes.…”
Section: Introductionmentioning
confidence: 69%
“…The MCRs could also introduce novel chemical structures and functions in the final products during the procedure of MCRs. More recently, the combination of controlled living polymerization and MCRs has also been demonstrated by Tao and co‐workers . Considered the above described characteristics, we could therefore expect that MCRs may be promising tools for fabrication of various multifunctional AIE‐active FONs in more efficient routes.…”
Section: Introductionmentioning
confidence: 69%
“…This feature provides a powerful possibility for the preparation of functional polyamide by the simple combinations of different components and alteration of different functional groups. Based on the recent investigations and our previous studies, the synthetic strategy for the multifunctional polyamides in this study is listed as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the Ugi reaction has been successfully used for the synthesis of structurally diverse polymer . Generally speaking, if we want to obtain polymers in a one‐pot via the Ugi reaction, the four components must contain one AB‐type component or two bifunctional AA‐type components .…”
Section: Ugi Reaction Of Amino Acids For γ‐ δ‐ and Poly(ε‐peptoid)smentioning
confidence: 99%